Динаміка пульсуючих центрифуг і обгрунтування шляхів підвищення їх надійності та продуктивності - Горошко, Ганна Олегівна (My University, 2003)
Дисертація на здобуття наукового ступеня кандидата технічних наук по спеціальності 05.18.12 — “Процеси та обладнання харчових, мікробіологічних та фармацевтичних виробництв”, Національний університет харчових технологій, Київ, 2003. Дисертація присвячена вивченню динаміки промислових пульсуючих центрифуг. The thesis presented for Candidate Degree in Technical Sciences (speciality 05.18.12 – processes and apparatus of food, microbiological and pharmaceutical productions), National University of Food Technologies, Kyiv, 2003. The thesis is devoted to investigation of industrial pulsing centrifuges dynamics. The equations of advancing and angular vibrations are formulated. Vibrations and dynamic stability and also pulsator motion are analysed. A mode of the pulsator motion, centrifuge mass centre motion law and possibility of resonances realisation for centrifuge vibrations are shown. An insensitivity of the centrifuge to parametric excitation and pulsator motion frequency constraints are established.
Keywords: пульсуючі центрифуги; вимушені коливання; параметричні коливання; стійкість руху; центрифуга; pulsing centrifuges; forced vibrations; parametric vibrations; motion stability; centrifuge